Total monomeric anthocyanin (TMA) extraction from mangosteen hull in ultrasonic assisted acidified aqueous solvent extractions - Cheok, Choon Yoong; Chin, Nyuk Ling; Yusof, Yus Aniza; A. Talib, Rosnita; Law, Chung Lim (Research Publishing Services, 2012)
The cavitation effects from ultrasonic waves are used to enhance the extraction of useful compounds from plant materials by disrupting the cells walls to improve extractability. This study looked into the effects of amplitude and time of sonication in enhancing total monomeric anthocyanin (TMA) recovery from mangosteen hull in acidified methanol and ethanol solvents. A clear quadratic trend of optimal sonication amplitude and time was observed when using methanol giving a maximum TMA of 5.82±0.35 mg cy-3-glu/g hull powder at 50% amplitude and 5 minutes. The improvement was less significant when using ethanol. In general, the amount of TMA obtained improved by 186.70% in aqueous methanol and 15.16% in aqueous ethanol.